Privatization in Italy 1993-2002: Goals, Institutions, Outcomes, and Outstanding Issues - Andrea Goldstein (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper describes the privatization program in Italy during the 1990s and puts that policy in the context of macroeconomic adjustment, general market deregulation, and promotion of private investment in the provision of public infrastructure. The wave of state divestitures reached Italy later than other OECD countries. A deep-rooted tradition of state intervention, coupled with the use of public enterprises as a source of employment and political support, hindered the timid attempts at privatization of the 1980s, delaying until 1992 the start of largescale privatizations. These were imposed on Italian politicians and electorate by a host of factors: the financial crisis affecting both the general government and, sometimes irreversibly, state-owned enterprises (SOEs); the increasing aversion of the European Commission towards state aid to ailing firms; and the discredit thrown on public enterprises by their involvement in corruption scandals. An evaluation of its results in manufacturing, performed on the basis of a set of operative and restructuring performance indicators for a representative sample of privatized firms, indicates the lack of statistically significant improvements in efficiency scores. The analysis of the consequences of privatization on corporate governance show that, notwithstanding considerable changes in the structure of ownership and a sizeable contribution to capitalization and liquidity growth, the market for corporate control remains insufficiently transparent. These results appear to relect multiple factors - the preference accorded to quantitative targets in the context of EMU convergence, the weakness of the executive and its dependence on shaky parliamentary majorities in the Italian political system, and finally the resistance of politicians to relinquish control over SOEs. In the broader framework of fiscal decentralization, this last factor seems if anything reinforced by recent normative changes and proposals.
Keywords: 330; privatization; regulatory reform; industrial restructuring; Italy